A Comparison with Analysis of the SADC FIP before and after Its Amendment - Kondo, Tinashe (My University, 2017)
Discourses on rights, duties and obligations predominantly take place within the context of constitutional, administrative and human rights law. In the last decade these debates have also begun to take place in international investment law, an "autonomous branch" of international law. The main debate centres on the adequacy and sustainability of investor-centred regulatory regimes which provide more rights than obligations to investors. The 2006 Southern African Development Community Finance and Investment Protocol (SADC FIP) was a typical example of such a regime. It offered antiquated protections which were characteristic of first generation Bilateral Investment Treaties (BITs). The result was that some countries, such as South Africa, opted not to conform to this binding instrument, which did not match their progressive vision of foreign investment. It is against this backdrop that the SADC FIP was recently amended. The amendment, balances the rights and obligations of investors and state parties to some degree, and moves towards sustainable foreign investment. However, this paper argues that more still needs to be done to modernise the document in line with more recent trends.
Keywords: A Comparison with Analysis of the SADC FIP before and after Its Amendment